2019
DOI: 10.1038/s41419-019-1497-1
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma cell intrinsic PD-L2 signals promote invasion and metastasis via the RhoA-ROCK-LIMK2 and autophagy pathways

Abstract: Known as co-stimulatory molecule, programmed death ligand-2 (PD-L2) contributes to T-cell exhaustion by interaction with programmed death-1 (PD-1) receptor, but its tumor cell-intrinsic signal effects have been little investigated. PD-L2 expression was detected by immunohistochemistry in 18 pairs of primary osteosarcoma tissues and matching lung metastasis tissues. We also investigated the effects of PD-L2 knockdown on osteosarcoma both in vitro and in vivo. In our study, PD-L2 expression was elevated in lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 60 publications
2
57
0
Order By: Relevance
“…PD-L1 regulates cancer cell resistance to apoptosis (22), cell proliferation, AKT/mTOR signaling pathway, and autophagy in ovarian cancer cells (13,15), while in vitro data, describing an intrinsic role of PD-L2 in cancer cells, are scarce. A recent study demonstrates that cell-intrinsic PD-L2 signals promote invasion and metastasis through the Rhoa-ROCK-LIMK2 and positively regulate autophagy pathways in osteosarcoma cells (14). In this study, we demonstrate that PD-L2 increases migration of the mixed type I/II PC-EM004b cell line, while the opposite effects were observed by PD-L2 silencing in the Ishikawa cell line, a type I model that expresses high levels of PD-L2.…”
Section: Discussionsupporting
confidence: 47%
See 4 more Smart Citations
“…PD-L1 regulates cancer cell resistance to apoptosis (22), cell proliferation, AKT/mTOR signaling pathway, and autophagy in ovarian cancer cells (13,15), while in vitro data, describing an intrinsic role of PD-L2 in cancer cells, are scarce. A recent study demonstrates that cell-intrinsic PD-L2 signals promote invasion and metastasis through the Rhoa-ROCK-LIMK2 and positively regulate autophagy pathways in osteosarcoma cells (14). In this study, we demonstrate that PD-L2 increases migration of the mixed type I/II PC-EM004b cell line, while the opposite effects were observed by PD-L2 silencing in the Ishikawa cell line, a type I model that expresses high levels of PD-L2.…”
Section: Discussionsupporting
confidence: 47%
“…PD-1 ligands are transmembrane proteins that binds PD-1 expressed on the cellular surface of activated T and B cells, monocytes, natural killer, and dendritic cells (23,35). Recent studies showed also an intracellular distribution, suggesting that these proteins might have an unexpected function, different from what has previously been described for its membranous counterpart (13,14,36,37). It has been demonstrated that cytoplasmic PD-L1 levels in SKOV3 and HO8910 ovarian cancer cell lines are high, and in SKOV3 cells, cytoplasmic PD-L1 increased cancer cell growth and migration (36).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations